Perceptions of a patient-staff-caregiver group among inpatients in a radiotherapy unit. Issue 4 (8th July 2014) - Mitnik, Inbal; Zalman, Daniela; Vorobeichik, Marina; Gurevich-Halevi, Michal; Eliasov, Liron; Lulav-Grinwald, Doron; Bar-Sela, Gil
Abstract Objective: Coping with cancer and its treatments has significant psychological implications for patients, and hospitalization can lead to emotional distress. Based on a community meeting (CM), a common therapeutic intervention in psychiatric wards, a unique patient–staff–caregiver group is held weekly on the radiotherapy unit of our hospital. The goals are to strengthen patient coping abilities and prompt open communications. The present study aimed at quantitatively estimating the effect of the community meeting by gauging the perceptions with respect to several therapeutic aspects. Method: A questionnaire was developed for patients who participated in CMs during their hospitalization based on four theoretical factors: illness perception, relations with the main caregiver, relations with other participants, and relations with unit staff. Results: Participants' general satisfaction with the meetings was found to be positive. The most significant aspect of the meetings, as perceived by participants, was relationships with the staff. Patients born in Israel perceived relationships with other participants more positively. Significance of results: Attentive interaction with medical staff and open communications are highly important for patients and contribute to their general satisfaction with the meetings.